Executive Committee Minutes 2021-04-01 - Academic Senate:::::::::
Agenda - Approved. Minutes of 3/11/2021 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice President for Student Affairs Report. Associated Students Report. APARC Report. Posthumous Degree Request for Lisa Dunwoody – Approved for Senate Agenda. EPC Report – question only. EPC Report. THAR Concentration in Dance Discontinuance – Approved for Senate Agenda. THAR Concentration in Acting Revision, THAR Concentration in Technical Theatre Revision, THAR Concentration in Theatre Studies Revision – Approved for consent calendar. SAC Report. CFA Report. Candidates for Graduation for Senate consent – Approved. From FSAC: Revision to the RTP policy – Approved for Senate Agenda. Senate Agenda approved.